(untitled) (International Journal of Physiotherapy, 2015)
Background: Muscle energy technique is used for restoring normal tone in hypertonic muscles, strengthening weak muscles, preparing muscle for subsequent stretching, one of the main uses of this method is to normalize joint range which may help in increase flexibility and performance in sprinters. The aim of the study is to evaluate the effect of muscle energy technique on flexibility of hamstrings and calf muscles and sprinting performance in sprinters. The objective of the study is to determine the muscle energy technique on hamstrings and calf muscle flexibility and sprinting performance in sprinters by using goniometer and timing of sprinting performance. Method: The study design is an experimental study in which 30 male sprinters were recruited in this study. The study sample included all male healthy sprinters, aged between 15 -30 years. All subjects received warm up, muscle energy technique and cool down exercises daily for a period of 6weeks.The outcome measures are 90°-90°popliteal angle for assessing hamstring flexibility and ROM of ankle joint for calf muscles by universal goniometer and sprinting performance time by using stopwatch. Results: Independent t-test and paired t- test are used to analyse the data. A significant difference was found between pre and post values of hamstring and calf muscle flexibility and sprinting performance after the analysis in this study. Conclusion: This study shows that there was a significant effect of MET on hamstring and calf muscle flexibility and sprinting performance.